The Effect of Pervious Concrete on Water Quality Parameters: A Case Study - Pilon, Brent S.; Tyner, John S.; Yoder, Daniel C.; Buchanan, John R. (Water (Basel), 2019)
Stormwater is a leading source of pollutants that when transported to surface waters may damage aquatic habitat, decrease reservoir capacity, and contaminate drinking water. In order to evaluate whether a pervious concrete detention system can remove stormwater pollutants from the runoff, water quality was monitored at a site with both impervious asphalt and pervious concrete parking areas. The stormwater flowed across asphalt pavement before infiltrating into the pervious concrete and an aggregate sub-base below. The runoff was sampled exiting the asphalt but prior to entering the pervious concrete, and after it passed through the pervious concrete detention system, representing pre- and post-treatment sampling. Results showed statistically significant (p < 0.05) decreases in concentrations of total suspended solids, nitrite, chemical oxygen demand, and polycyclic aromatic hydrocarbons compared to untreated asphalt runoff. Zinc concentrations were apparently reduced, but not quite to statistically significant levels (p = 0.054). Values of pH and sulfate both showed statistically significant (p < 0.05) increases.